Unveiling the Link between Principal Leadership and School Climate in Promoting Deep Learning: The Mediating Role of Teacher Collaboration - Sarwo Edy; Wannaporn Siripala; Mustakim Mustakim; Irwani Zawawi (Universitas Muhammadiyah Mataram, 2026)
It has been relatively scarce regarding empirical evidence on how principal leadership and school climate jointly promote deep learning through the mediating role of teacher collaboration, particularly in school contexts where collaborative professional practices are still developing. This study aims to examine the effect of principal leadership on school climate through teacher collaborative culture as a mediating variable in public senior high schools in East Java, Indonesia. This study employed an explanatory quantitative approach using a survey method. Data were collected from 1,726 respondents, and after a rigorous data screening process, 1.206 valid responses were retained for analysis. The data for this study were collected using a structured questionnaire designed to measure four key constructs: principal leadership, teacher collaborative culture, school climate, and deep learning. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that principal leadership has a significant effect on teacher collaborative culture (β = 0.685, t = 39.368, p < 0.001) and school climate (β = 0.457, t = 16.470, p < 0.001). Teacher collaborative culture also significantly influences school climate (β = 0.481, t = 17.548, p < 0.001) and acts as a partial mediator (β = 0.330, t = 16.588, p < 0.001). This study extends educational leadership theory by showing that principal leadership promotes deep learning through school climate and teacher collaboration. It highlights teacher collaboration as a key mediating mechanism linking leadership practices to meaningful learning. Practically, the findings suggest that school leaders should foster supportive climates, shared instructional goals, and collaborative teacher cultures to strengthen deep learning practices and improve students’ critical, reflective, and constructive engagement.